Abiraterone-induced refractory hypokalaemia and torsades de pointes in a patient with metastatic castration-resistant prostate carcinoma: a case report. Issue 12 (16th November 2021) - Riad, Mariam; Allison, Jeffery Scott; Nayyal, Shahla; Hritani, AbdulWahab
Abstract: Background: Abiraterone, an androgen deprivation therapy, has been used in the treatment of metastatic castration-resistant prostate cancer (mCRPC). It has been associated with increased risks of hypokalaemia and cardiac disorders. We report a case of torsades de pointes (TdP) associated with abiraterone use and refractory hypokalaemia in a man with mCRPC. Case summary: A 78-year-old man with mCRPC presented to the emergency room for generalized weakness. Laboratory results revealed a potassium level of 2.2 mmol/L (3.5–5.0), magnesium level of 2.4 mg/dL (1.6–2.5), and normal kidney and hepatic functions. Initial electrocardiogram showed atrial fibrillation with rapid ventricular rate of 106 b.p.m., frequent premature ventricular contractions, and a QTc of 634 ms. The patient had multiple episodes of TdP, became pulseless and underwent advanced cardiac life support, including defibrillation. Despite a total of 220 mEq of intravenous potassium chloride, his potassium level only improved to 2.8 mmol/L. He received spironolactone and amiloride to promote urinary potassium reabsorption in addition to hydrocortisone, in an effort to reduce abiraterone's effect on increasing mineralocorticoid synthesis. Discussion: Abiraterone has been widely used in mCRPC since its approval by the Food and Drug Adminstration in 2011. Regulatory guidelines and standardized close QTc and electrolyte monitoring in patients may help prevent fatal arrhythmias associated with abiraterone.